Sistem Pendukung Keputusan untuk Menentukan Pemberian Beasiswa Menggunakan Metode Simple Additive Weighting (SAW) pada Sekolah MTs Mathlaul Anwar - Winarti, Wiwin; Nurhayati, Nurhayati; Vindua, Raditia (Teknik Informatika Universitas Pamulang, 2021)
Scholarship means an assistance given to individuals (students) which aims to be used for the continuation of the education taken. Every year, MTS Mathlaul Anwar provides scholarships to outstanding students. The current selection of scholarships, which is still done manually, makes schools need to determine a clear way of calculating which students get the right scholarships so that the scholarships given are right on target. Therefore, a Decision Support System (SPK) application is designed which is expected to be able to determine scholarship recipients according to the qualifications determined by the school. SPK is expected to help select scholarship recipients. The existence of the proposed SPK can help schools in the selection process for scholarships easily, quickly and accurately. In this study, the author uses the Simple Additive Weighting (SAW) method which can provide assessment results based on each weight on each scholarship award qualification. The criteria for awarding scholarships are the value of knowledge, the value of skills, activeness in school activities (ex-curricular activities), attendance and morals. By making a decision support system by applying the SAW method, it is easier for schools to determine students who get scholarships. Of the five selected scholarship recipients, student D was found to be in the first rank with a result of 14.25.